High-precision bionic anti-drag structure preparation process, anti-drag material and anti-drag structure

By spraying the drag-reducing material on the surface of the ship and performing light curing and thermal curing treatment, the problem of difficulty in spraying the three-dimensional shield scale structure in the prior art is solved, and a high-precision and long-term drag-reducing effect is achieved.

CN119614063APending Publication Date: 2025-03-14NANJING CITY CARENS SHIP EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909933.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to spray three-dimensional shield scale structures on the surface of ships, resulting in high production difficulty and poor finished product accuracy.

Method used

A high-precision bionic drag-reducing structure preparation process is adopted. By opening a shield scale structure groove on the transparent silicone film, the drag-reducing material is injected, and a high-precision drag-reducing structure is formed through two steps: light curing and heat curing.

Benefits of technology

The three-dimensional structure is realized with high-precision spraying on the surface of the ship, which improves the hardness, peel strength and wear resistance of the drag-reducing material, and ensures the long-term drag-reducing effect of the drag-reducing structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614063A_ABST
    Figure CN119614063A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of resistance reduction, and particularly discloses a high-precision bionic resistance reduction structure preparation process, a resistance reduction material and a resistance reduction structure. According to the method, polyurethane acrylate, fluorine-containing acrylate, epoxy acrylate and an active diluting monomer are used as main raw materials of a resistance reducing material, the resistance reducing material is injected into a placoid scale structure groove of a transparent flexible silica gel mold, a UV curing mode is adopted firstly, so that a resistance reducing structure is formed preliminarily, and then the resistance reducing material is formed; the drag reduction material can be directly and preliminarily cured on the surface of the ship; and then thermal curing treatment is carried out in the later period, the drag reduction material is fully crosslinked in the thermal curing treatment process, and the hardness, peel strength and wear resistance of the drag reduction material are improved. The technical blank of spraying a three-dimensional structure on the surface of a ship is filled, high pattern precision is ensured, the integrity of the three-dimensional pattern can still be ensured after long-term use, and the resistance reduction structure has a long-acting resistance reduction effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of drag reduction, and more specifically, to a high-precision bionic drag reduction structure preparation process, a drag reduction material and a drag reduction structure. Background Art

[0002] Ships are mainly affected by water resistance during navigation, and effectively overcoming water resistance is the key to increasing the speed of ships. The industry generally adopts the method of coating drag-reducing coating on the surface of the hull to increase the navigation speed by reducing the friction resistance of the hull underwater. The drag-reducing coating is attached to the surface of the hull by two mainstream methods: spraying or film attachment. At present, the applicant has made relevant research in the field of drag reduction, using bionic technology: drawing on the fine shield scale structure covering the surface of sharks, the ridge-like protrusions in the shield scale structure are called ribs, and the ribs form arc-bottomed grooves. This groove structure has a good drag reduction effect.

[0003] Since the shield scale structure is relatively complex and difficult to manufacture, conventional spraying methods can only spray a smooth plane on the ship surface, and it is difficult to directly spray a three-dimensional structure on the ship surface. Summary of the invention

[0004] In order to solve the problems of high difficulty in manufacturing shield scale structures and poor precision of finished products, the present application provides a high-precision bionic drag reduction structure preparation process, drag reduction material and drag reduction structure.

[0005] In the first aspect, the present application provides a high-precision bionic drag reduction structure preparation process, which adopts the following technical solution: The high-precision bionic drag reduction structure preparation process includes the following steps: Preparation of spraying membrane material: several groups of shield scale structure grooves are opened on the transparent silicone membrane material; Spray curing: inject the drag reduction material into the shield scale structure groove, first light cure, then heat cure to obtain the drag reduction structure; The drag reduction material is composed of the following raw materials in parts by weight: 100 parts of polyurethane acrylate, 5-10 parts of fluorine-containing acrylate, 25-40 parts of epoxy acrylate, 15-35 parts of active diluent monomer, 2-4 parts of photoinitiator, 3-6 parts of thermal initiator and 0.1-1 part of auxiliary agent.

[0006] Furthermore, the functionality of the polyurethane acrylate is 2-3.

[0007] Furthermore, the viscosity of the polyurethane acrylate is 5000-20000 cps.

[0008] Furthermore, the fluorine-containing acrylate is perfluorooctyl ethyl acrylate.

[0009] Furthermore, the acid value of the epoxy acrylate is 3 to 5 mgKOH / g.

[0010] Furthermore, the viscosity of the epoxy acrylate is 1000 to 25000 cps.

[0011] Furthermore, the active diluent monomer is any one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, tetrahydrofurfuryl acrylate and ethoxyethoxyethyl acrylate.

[0012] Furthermore, the photoinitiator is a liquid free radical type I photoinitiator.

[0013] Furthermore, the liquid free radical type I photoinitiator is ethyl 2,4,6-trimethylbenzoylphosphonate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone and a mixture of benzoyl formate.

[0014] Furthermore, the thermal initiator is pentaerythritol tetrakis-3-mercaptopropionate and / or trimethylolpropane tris(3-mercaptopropionate).

[0015] Furthermore, the auxiliary agent includes an antioxidant, an ultraviolet absorber, a defoaming agent, a leveling agent, and an adhesion promoter.

[0016] Furthermore, before the spraying and curing step, the surface of the ship is cleaned and polished using 300-400 mesh sandpaper.

[0017] In a second aspect, the present application provides a drag reduction material, which adopts the following technical solution: A drag reducing material is the drag reducing material used in the above-mentioned high-precision bionic drag reducing structure preparation process.

[0018] In a third aspect, the present application provides a drag reduction structure, which adopts the following technical solution: A drag reduction structure is manufactured using the aforementioned high-precision bionic drag reduction structure preparation process, comprising a main ridge and a plurality of secondary ridges, wherein each pair of the secondary ridges are symmetrically distributed about the main ridge, the same pair of secondary ridges have the same shape and size, and the spacing between the same pair of secondary ridges and the main ridge is the same; the height and length of the main ridge are both greater than those of the secondary ridges, and the height and length of the secondary ridges on the same side gradually decrease in a direction away from the main ridge; a groove is formed between two adjacent ridges.

[0019] This application has at least the following advantages: First, this application fills the technical gap of spraying three-dimensional structures on the surface of ships. Polyurethane acrylate, fluorinated acrylate, epoxy acrylate and active diluent monomer are used as the main raw materials; the overall viscosity of the drag reduction material is moderate, and it is injected into the shield scale structure groove of the transparent flexible silicone mold, filled and cured, and under the action of the photoinitiator, UV curing is first used to make the drag reduction structure initially formed, and the drag reduction material can be directly cured on the surface of the ship; due to the rapid curing of the drag reduction material, the drag reduction material is reduced from flowing slightly due to the effect of gravity during the curing process; the drag reduction material is thermally cured in the later stage, and the drag reduction material is fully cross-linked during the thermal curing process, which improves the hardness, peeling strength and wear resistance of the drag reduction material.

[0020] Second, polyurethane acrylate, fluorinated acrylate and epoxy acrylate all contain acrylate groups, and the structural similarity helps the three to have a certain degree of compatibility; at the same time, polyurethane acrylate contains a long-chain polyol soft segment, which provides good flexibility and elasticity, giving the drag reduction structure a certain toughness; fluorinated acrylate provides a fluorine group with low surface energy, and the introduction of fluorinated side chains reduces the hydrophobic and oil-repellent properties of the drag reduction structure; the fluorinated side chain has microscopic incompatibility with the resin, forming a microscopic phase separation during the thermal curing process, effectively absorbing the impact energy, and improving the impact strength of the drag reduction structure; epoxy acrylate gives the drag reduction structure a certain hardness, and a strong chemical bond is formed between the epoxy group and the substrate, which can give the drag reduction structure a higher peel strength, making up for the problem of decreased peel strength caused by the introduction of fluorinated side chains, so that the drag reduction structure can be stably attached to the surface of the ship substrate. The drag reduction structure has excellent mechanical properties, wear resistance and impact resistance, and can still ensure the integrity of the three-dimensional pattern under long-term use. The drag reduction structure has a long-term drag reduction effect.

[0021] Third, optimize the viscosity, functionality, acid value and other related parameters of polyurethane acrylate, fluorinated acrylate and epoxy acrylate in the drag reduction material, so that the drag reduction material can infiltrate the plastic surface, optimize the mechanical properties, peel strength and processability of the drag reduction structure, so that the flow rate of the drag reduction material matches the curing rate during construction and spraying, and improve the processing accuracy of the drag reduction structure. At the same time, the curing shrinkage of the drag reduction material is reduced, which has little effect on the stability of the drag reduction structure on the ship.

[0022] Fourth, before spraying and curing, the surface of the ship is pretreated to remove dust, stains and other substances on the surface of the ship, and at the same time increase the surface roughness of the ship, so that the drag reduction structure can be more firmly and stably attached to the surface of the ship. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A top view of the drag reduction structure formed in Example 1 of the present application; Figure 2It is a schematic diagram of the cross-sectional structure of the drag reduction structure in the main viewing direction.

[0024] Figure 3 It is a TPU substrate with a drag reduction structure.

[0025] Figure numerals: 1, main ridge; 2, secondary ridge. DETAILED DESCRIPTION

[0026] Unless otherwise specified, the sources of raw materials involved in the following examples and comparative examples are as follows: Polyurethane acrylate: Brand: RU-2041B, functionality is 2, viscosity is 12000~20000cps, acid value is <2 mgKOH / g; Brand: RU-3172B, functionality 3, viscosity 6000-18000cps, acid value <3 mgKOH / g; Brand: RU-637B, functionality 6, viscosity 15000-20000cps, acid value <1mgKOH / g; Fluorinated acrylate: purity> 98%, sourced from Jinan Guochen Taifu Chemical Co., Ltd.; Epoxy Acrylate: Brand: RV-1036, functionality is 2, viscosity is 8000-25000cps, acid value is <5 mgKOH / g; Brand: RV-1001A, functionality is 2, viscosity is 1000-2500cps, acid value is <3 mgKOH / g; Brand: RV-1016, functionality is 2, viscosity is 50000~80000cps, acid value is <5mgKOH / g; Photoinitiator: Brand: photoinitiator 1173, analytical grade; Thermal initiator: Brand: 2-ethyl-4-methylimidazole, liquid, analytical grade; Antioxidant: Brand: Antioxidant 1010, analytical grade; Ultraviolet absorber: Brand: UV-531, analytical grade; Adhesion promoter: Brand: CP-343-1, solid content 100%; Leveling agent: Brand: DH-3170; Defoaming agent: brand BYK-066N.

[0027] Example 1

[0028] A drag reduction structure, the structure of which is shown in Figure 1 and Figure 2: It includes a main ridge and 2 pairs of secondary ridges, each pair of secondary ridges is axially symmetrical about the main ridge; the same pair of secondary ridges have the same shape and size, and the distance between the same pair of secondary ridges and the main ridge is the same; the height and length of the main ridge are both greater than the secondary ridges, the length of the secondary ridges on the same side gradually decreases in the direction away from the main ridge, and the height of the secondary ridges on the same side gradually decreases in the direction away from the main ridge; more specifically, the length of the main ridge is set to 5cm, the length of one pair of secondary ridges is 3cm, and the height of the other pair of secondary ridges is 1cm; the width of the main ridge and the secondary ridges are both 5mm; the height of the main ridge is 5mm, the length of one pair of secondary ridges is 3mm, and the height of the other pair of secondary ridges is 1mm; the spacing between two adjacent ridges is 5mm.

[0029] The above drag reduction structure is formed by a drag reduction material, and the drag reduction material is composed of the following raw materials in parts by weight: 100 parts of polyurethane acrylate RU-2041B, 8 parts of perfluorooctyl ethyl acrylate, 30 parts of epoxy acrylate RV-1036, 20 parts of n-butyl acrylate monomer, 4 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 6 parts of pentaerythritol tetrakis-3-mercaptopropionate, 0.2 parts of antioxidant 1010, 0.2 parts of ultraviolet absorber UV-531, 0.2 parts of defoamer BYK-066N, 0.2 parts of leveling agent DH-3170 and 0.2 parts of adhesion promoter CP-343-1; Follow these steps to make it: Pretreatment: clean the ship surface, polish it with 400-grit sandpaper, rinse and dry it after polishing; Preparation of spraying membrane material: a plurality of shield scale structure grooves are opened on a transparent silicone membrane material (transparent silicone membrane material). The shape and size of the shield scale structure grooves are the same as the above-mentioned drag reduction structure. The top of the shield scale structure groove is connected to the outside world so that the drag reduction material can be injected into the shield scale structure groove; and each group of shield scale structure grooves can be arranged in a matrix or in a staggered arrangement; Spray curing: Inject the drag reduction material into the shield scale structure groove, and then irradiate it with ultraviolet light at an intensity of 20mW / cm 2 After curing for 5 minutes, it is baked and heated for curing at a baking temperature of 120°C and a curing time of 10 minutes to obtain a drag reduction structure.

[0030] Example 2-3 A drag reduction structure, which differs from Example 1 in that the weight portions of the various components of the drag reduction material are different, as follows: In Example 2, 100 parts of polyurethane acrylate RU-2041B, 5 parts of perfluorooctyl ethyl acrylate, 25 parts of epoxy acrylate RV-1036, 15 parts of n-butyl acrylate monomer, 2 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 3 parts of pentaerythritol tetrakis-3-mercaptopropionate, 0.05 parts of antioxidant 1010, 0.05 parts of ultraviolet absorber UV-531, 0.05 parts of defoamer BYK-066N, 0.05 parts of leveling agent DH-3170 and 0.05 parts of adhesion promoter CP-343-1; In Example 3, 100 parts of polyurethane acrylate RU-2041B, 10 parts of perfluorooctyl ethyl acrylate, 40 parts of epoxy acrylate RV-1036, 35 parts of n-butyl acrylate monomer, 4 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 6 parts of pentaerythritol tetrakis-3-mercaptopropionate, 0.2 parts of antioxidant 1010, 0.2 parts of ultraviolet absorber UV-531, 0.2 parts of defoamer BYK-066N, 0.2 parts of leveling agent DH-3170 and 0.2 parts of adhesion promoter CP-343-1.

[0031] Embodiment 4-5 A drag reduction structure, which differs from Example 1 in that the viscosities of polyurethane acrylate and epoxy acrylate are different, as follows: In Example 4, RU-3172 was used in place of RU-2041B in equal parts by weight, and RV-1036 was used in place of RV1001A in equal parts by weight; In Example 5, RU-637B was used in equal parts by weight instead of RU-2041B, and RV-1016 was used in equal parts by weight instead of RV1001A.

[0032] Embodiment 6-7 A drag reduction structure, which differs from Example 1 in that the spray curing parameters in the preparation step are different, as follows: In the spray curing step of Example 6, the drag reducing material is injected into the shield scale structure groove, and then irradiated with ultraviolet light at an irradiation intensity of 10 mW / cm 2 After curing for 1 minute, it is baked and heated for curing at a temperature of 140°C and a curing time of 30 minutes to obtain a drag reduction structure; In the spray curing step of Example 7, the drag reducing material is injected into the shield scale structure groove, and then irradiated with ultraviolet light at an intensity of 20 mW / cm 2 After curing for 10 minutes, it is baked and heated for curing at a baking temperature of 100°C and a curing time of 5 minutes to obtain a drag reduction structure.

[0033] Comparative Example 1 A drag reduction structure, which differs from Example 1 in that only thermal curing is selected during the spray curing process: the drag reduction material is injected into the shield scale structure groove, and immediately baked and heated for curing. The baking temperature is 140°C and the curing time is 30 minutes to obtain a drag reduction structure.

[0034] Comparative Example 2 A drag reduction structure, which differs from Example 1 in that only light curing is selected during the spray curing process: the drag reduction material is injected into the shield scale structure groove, and then irradiated with ultraviolet light at an irradiation intensity of 20 mW / cm 2 , and cured for 30 minutes to obtain a drag reduction structure.

[0035] Comparative Example 3 A drag reduction structure, which differs from Example 1 in that epoxy acrylate RV-1036 is used in equal parts by weight in the drag reduction material instead of polyurethane acrylate.

[0036] Comparative Example 4 A drag reduction structure, which differs from Example 1 in that polyurethane acrylate RU-2041B is used in the drag reduction material in equal parts by weight to replace perfluorooctyl ethyl acrylate.

[0037] Comparative Example 5 A drag reduction structure, which differs from Example 1 in that polyurethane acrylate RU-2041B is used in equal parts by weight in the drag reduction material instead of epoxy acrylate.

[0038] Performance Testing

[0039] 1.Qualification rate: The TPU substrate is placed vertically to simulate the surface state of a ship hull; the drag reduction structure is printed on the vertical TPU substrate using the methods described in Examples 1-7 and Comparative Examples 1-5. Figure 3 , Figure 3 It is a TPU substrate with a drag reduction structure. There are multiple drag reduction structures on the surface of the TPU substrate, and the multiple drag reduction structures are arranged in a staggered manner.

[0040] Observe the integrity and accuracy of the printed pattern: take a single drag reduction structure as the calculation unit, and a qualified unit is one that does not have many undesirable conditions such as flow deformation, shrinkage deformation, adhesion between ridges, and separation between ridges and substrate; The percentage of qualified units on the TPU substrate to the total number is counted, and this percentage is the qualified rate.

[0041] 2. Stability: Place the TPU substrate with a drag reduction structure into a circulating water simulation test box, add a small amount of fine sand into the circulating water, set the inlet flow rate of the circulating water to 8m / s, simulate the external force impact on the ship at normal speed, and test for 3 hours. Observe the degree of surface damage of the TPU substrate with a drag reduction structure after 3 hours, and recalculate the qualified rate; the higher the qualified rate, the better the stability.

[0042] 3. Drag reduction rate: A TPU substrate with a smooth surface was used as the control group; the test conditions were controlled to be the same in a circulating water simulation test chamber, and the drag reduction rate of the TPU substrate with a drag reduction structure (after a stability test) was calculated through the change in the inlet and outlet pressure difference.

[0043] Table 1. Performance test data of Examples 1-7 and Comparative Examples 1-5

[0044] According to the test data, we can see that: First, comparative example 1 only uses thermal curing treatment, and the pattern qualification rate is lower than that of example 1, and some drag reduction structures have deformation, flow and the like. After high-speed impact of water containing fine sand, the pattern qualification rate dropped significantly and the stability became worse. At the same time, after actual testing, the drag reduction rate was low, only 11%. This proves that: the thermal curing time is long, and the drag reduction coating has a flow problem, especially at the edge of the TPU substrate, which is far from the heat source and the flow problem is more serious. However, comparative example 1 has better stability, and after stability testing, the qualification rate did not drop much. However, due to the low qualification rate and poor precision of the drag reduction structure made in comparative example 1, the drag reduction rate is low, and a good drag reduction effect is not achieved.

[0045] Second, in Comparative Example 2, only photocuring treatment was used, and the pattern qualification rate was not much different from that in Example 1. However, after the stability test of Comparative Example 2, the decline in qualification rate increased. Finally, after actual testing, the drag reduction rate after the stability test was reduced to 9%. This proves that: when only photocuring treatment is used, the crosslinking density between polyurethane acrylate, perfluorooctyl ethyl acrylate and epoxy acrylate is low, and the degree of curing is limited, resulting in a decrease in the adhesion, strength and wear resistance of the drag reduction structure on the TPU substrate, and a large amount of damage to the drag reduction structure. The drag reduction effect of the drag reduction structure is deteriorated.

[0046] Third, there is a lack of polyurethane acrylate in Comparative Example 3, a lack of fluorinated acrylate in Comparative Example 4, and a lack of epoxy acrylate in Comparative Example 5; the initial pattern pass rate of Comparative Example 3 is low, and observation of its surface shows that most of the unqualified drag reduction structural units show large shrinkage, resulting in different degrees of separation and cracking problems of the drag reduction structural units. Although the initial pattern pass rate of Comparative Example 4 is high, after the stability test, it is found that its pattern pass rate has dropped significantly, indicating that fluorinated acrylate can absorb impact force and improve the stability of the drag reduction structure. At the same time, the drag reduction rate of Comparative Example 4 has dropped significantly, and the hydrophobic and oleophobic properties of the drag reduction structure have decreased. The pass rate of Comparative Example 5 has dropped significantly after the stability test, the reason for which is that the adhesion strength of the drag reduction structure is insufficient, and some ridges are prone to fall off.

[0047] Fourth, Examples 1-3 form a single comparison, and the main difference is that the ratios of polyurethane acrylate, perfluorooctyl ethyl acrylate and epoxy acrylate are different. In Example 2, the amount of perfluorooctyl ethyl acrylate and epoxy acrylate added is low, the initial state qualified rate of Example 2 is low, the qualified rate after the stable test decreases more, and the drag reduction rate is significantly reduced. In Example 3, the amount of perfluorooctyl ethyl acrylate and epoxy acrylate added is high, but the initial state qualified rate of Example 3 is low. The reason is that perfluorooctyl ethyl acrylate and epoxy acrylate cause greater shrinkage, resulting in deformation of part of the drag reduction structure.

[0048] Fifth, Examples 4 and 5 form a single comparison, and the main difference lies in the different selections of polyurethane acrylate and epoxy acrylate. The viscosity of polyurethane acrylate and epoxy acrylate in Example 4 is relatively low, and Example 4 is more prone to flow, resulting in a decrease in the pattern qualification rate. The viscosity of polyurethane acrylate and epoxy acrylate in Example 5 is relatively high, and the flow difficulty of the drag reduction material in the shield scale groove in Example 5 is increased, resulting in some shield scale grooves not being filled evenly, and the initial pattern qualification rate is reduced.

[0049] Sixth, Examples 6-7 form a single comparison, and the main difference lies in the different parameters of thermal curing and light curing. In Example 6, the light curing intensity and irradiation time were reduced, but the heat curing temperature and time were increased accordingly, and the qualified rate in the initial state was reduced. By observing the drag reduction structure, it can be found that higher heat curing temperatures can easily cause a substantial shrinkage of the drag reduction material. In Example 7, the light curing irradiation intensity and irradiation time were increased, and the heat curing temperature and time were decreased, and the qualified rate after the stability test dropped significantly. It shows that increasing the light curing irradiation intensity and time still cannot fully cure the drag reduction material.

[0050] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0051] Moreover, the above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A high-precision bionic drag reduction structure preparation process, characterized in that: The steps include: Preparation of spraying membrane material: several groups of shield scale structure grooves are opened on the transparent silicone membrane material; Spray curing: inject the drag reduction material into the shield scale structure groove, first light cure, then heat cure to obtain the drag reduction structure; The drag reduction material is composed of the following raw materials in parts by weight: 100 parts of polyurethane acrylate, 5-10 parts of fluorine-containing acrylate, 25-40 parts of epoxy acrylate, 15-35 parts of active diluent monomer, 2-4 parts of photoinitiator, 3-6 parts of thermal initiator and 0.1-1 part of auxiliary agent.

2. The high-precision bionic drag reduction structure preparation process according to claim 1, characterized in that: The functionality of the polyurethane acrylate is 2-3.

3. The high-precision bionic drag reduction structure preparation process according to claim 2, characterized in that: The viscosity of the polyurethane acrylate is 5000-20000 cps.

4. The high-precision bionic drag reduction structure preparation process according to claim 1, characterized in that: The fluorine-containing acrylate is perfluorooctyl ethyl acrylate.

5. The high-precision bionic drag reduction structure preparation process according to claim 1, characterized in that: The acid value of the epoxy acrylate is 3 to 5 mgKOH / g.

6. The high-precision bionic drag reduction structure preparation process according to claim 5, characterized in that: The viscosity of the epoxy acrylate is 1000-25000 cps.

7. The high-precision bionic drag reduction structure preparation process according to claim 1, characterized in that: The active diluent monomer is any one or more of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, tetrahydrofurfuryl acrylate and ethoxyethoxyethyl acrylate.

8. The high-precision bionic drag reduction structure preparation process according to claim 1, characterized in that: Before the spraying and curing step, the surface of the ship is cleaned and polished using 300-400 mesh sandpaper.

9. A drag reducing material, characterized in that: The drag reducing material is used in the process for preparing the high-precision bionic drag reducing structure as described in any one of claims 1 to 8.

10. A drag reduction structure, characterized in that: The method comprises the following steps: the method is manufactured by the high-precision bionic drag reduction structure preparation process described in any one of claims 1 to 8, comprising a main ridge (1) and a plurality of secondary ridges (2), wherein each pair of the secondary ridges (2) are symmetrically distributed about the main ridge (1), the same pair of secondary ridges (2) have the same shape and size, and the same pair of secondary ridges (2) have the same spacing with the main ridge (1); the height and length of the main ridge (1) are both greater than those of the secondary ridges (2), and the height and length of the secondary ridges (2) on the same side gradually decrease in a direction away from the main ridge (1); and a groove is formed between two adjacent ridges.